The Bidster peer-to-peer auction system - Camaclang, Kristoffer Carlo (2003)
Existing auction systems rely on a centralized server acting as a middleman between users to facilitate the operations required to run such an application. This is detrimental to the system since use of the application in such a configuration becomes more costly in terms of time and money. It also congests the network and makes the entire system totally dependent on the reliability of the server. We believe that the solution lies in the form of the Bidster Peer-to-Peer Auction System. Bidster aims to provide an accessible venue for procurement, eliminating the need for a centralized server and utilize open source platforms in order to provide users with an auction system that is convenient, efficient, and economical.